MODEL KERJASAMA ANTAR DAERAH DALAM PENYELESAIAN SENGKETA KEWENANGAN PADA DAERAH KABUPATEN/KOTA HASIL PEMEKARAN - Muhammad Fauzan; Kadar Pamuji (Jurnal Media Hukum, 2014)
The title of this study is a model of inter-regional cooperation in the Settlement Authority In District / Municipal Expansion. This research is motivated many conflicts / disputes regarding both the authority on government affairs and other matters between the Regional Holding with areas of the division. Results of the study include, first, the policy of regional expansion in addition to having the advantage in matters relating to the acceleration and improvement of public services and also has brought the potential development that could affect the relationship between regional harmonization with the Regional Holding Redistricting results, primarily due to a conflict of authority on asset management area. Second, the model of inter-regional cooperation in resolving disputes between the authority of the regency / municipality division of the District Holding wear two (2) approach, which is a formal legal approach and local wisdom approach, namely by providing “touch” argument that “touch” people’s emotional, the use of the term “interests of the whole community and mutual respect” with no regard to administrative boundaries of the Regional District of Holding and Expansion Results. This means that the interests of the community should be encouraged regardless of whether the incoming administration in the District or Regional Expansion.